Detecting underground structures in Cyprus using field spectroscopy - Melillos, George; Themistocleous, Kyriacos; Agapiou, Athos; Michaelides, Silas; Hadjimitsis, Diofantos G. (My University, 2018)
Satellite remote sensing is considered as an increasingly important technology for detect underground structures. It can be applied to a wide range of applications as shown from various researchers. However, there is a great need to integrate information from a variety of sources, sent at different times and of different qualities using remote sensing tools. This paper presents the results obtained from field spectroradiometric campaigns at âburied' underground structures in Cyprus. A SVC-HR1024 field spectroradiometer was used and in-band reflectances were determined for medium and high resolution satellite sensors, including Landsat. A number of vegetation indices such as the Normalized Difference Vegetation Index (NDVI), Simple Ratio (SR) and Enhanced Vegetation Index (EVI) were utilized for the development of a vegetation index-based procedure aiming at the detection of underground military structures by using existing vegetation indices or other in-band algorithms. In this study, test areas were identified, analyzed and modeled under different scenarios, including: (a) the âñatural state' of the underground structure; (b) the different type of crop over the underground structure and imported soil; (c) the different types of non-natural material over the underground structure. A reference target in the nearby area was selected as a baseline.
Keywords: Military Underground Structures; Spectroscopy; Vegetation Indices